ATTENTION DEFICIT HYPERACTIVITY DISORDER SYMPTOMS IN ADULTS WITH ESSENTIAL TREMOR - Oguzturk, Omer; Alpua, Murat; Ulusoy, Ersin Kasim (MNJ (Malang Neurology Journal), 2022)
Background: Essential tremor is the most common movement disorder. İn this disease, which is characterized by tremor that increases with action and passes at rest, different accompanying symptoms can also be seen.Objective: The purpose of this study was to investigate attention deficit hyperactivity symptoms in adults with ET.Methods: Fifty six essential tremor patients and 56 controls were included in the study. Patients were recruited from outpatient clinic at Kirikkale University Medicine Faculty.  An informed consent form was signed by each patient after detailed information. Institutional ethics committee approval was obtained. Patients’ characteristics such as education level, gender, age and disease duration were recorded. Symptoms of ADHD in patients and controls were determined by using the Adult Report Deficit / Hyperactivity Disorder Self Report Scale. Short Form-36 and Hospital Anxiety and Depression Scale were also performed. Essential tremor severity was determined by using the Whiget essential tremor scale.Results: Essential tremor patients had significantly higher rate of Adult Attention Disorder Self-Report Scale Deficit/Hyperactivity scores compared to controls. Scores of Adult Attention Deficit/Hyperactivity Disorder Self-Report Scale were associated with depression and anxiety scores and physical and mental component scores of Short Form-36 in bivariate analyses. There was a positive correlation between tremor severity and ASRS scores( ASRS A scores= 17,3±5,5, p=0,032, ASRS B scores= 27,7±6,7,p=0,043, ASRS T scores= 45±12,2, p=0,017) however there was no significant statistical relationship between the duration of disease and ASRS scores.Conclusion: This study showed that ADHD symptoms can be observed in adult essential tremor patients and this may be associated with increased psychosocial morbidity and lowered quality of life in ET patients.